RELATIONS BETWEEN THE ABILITY OF MATHEMATICAL CREATIVE THINKING AND INTEREST IN LEARNING MATHEMATICS HIGH SCHOOL STUDENTS USING THE METHOD OF DISCOVERY LEARNING THROUGH RECIPROCAL TEACHING APPROACH - Bima Gusti Ramadan; Muhammad Yusuf Firdaus; Rippi Maya ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2019)
This research aims to elucidate how the relations between the ability of mathematical creative thinking with the learning interest of students in learning using the method of discovery learning through reciprocal teaching approach. The methods used in this research is a method of experimentation with the design of the control group pretes postes. The population in this research is the entire SMAN in Cimahi City, whereas samples randomly taken class. Class XI IPA 1 was selected as experiments class and Class XI IPA 2 was selected as the class of the control. Experiments Class given learning method using discovery learning through reciprocal teaching approach while the control classes are given convensional learning. Research results showed the existence of a significant relationship between the ability of mathematical creative thinking and learning interest of students in learning mathematics.